ANTESEDEN CONSUMERS’ ATITTUDE TERHADAP ADVERTISING DI KOTA BATAM - Golan Hasan (Jurnal Manajemen dan Pemasaran Jasa, 2017)
This study uses credibility, informative, hedonic/ pleasure and good for economy to analyze the effect of the consumers' attitude towards advertising. Methodology of data collection is done by attitude scale using questioner with the number of respondents as many as 300 sheets distributed. The results showed that credibility, informative, hedonic/ pleasure and good for economy simultaneously have significant effect on the consumers' attitude towards advertising. Credibility has positive and significant effect on consumers' attitude towards advertising. Informative has positive and significant effect on the consumers' attitude towards advertising. Hedonic/ pleasure has positive and significant effect on the consumers' attitude towards advertising. Good for economy has positive and significant effect on the consumers' attitude towards advertising.